AKTIVITAS HEPATOPROTEKTOR SARI BUAH LABU KUNING (Cucurbita moschata Duchesne.) PADA TIKUS (Rattus norvergicus) YANG DIINDUKSIKAN KARBON TETRAKLORIDA - Indrawan Aditya; Ihwan Ihwan; Jamaluddin Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy), 2016)
One of the plants that are often used in traditional medicine is the fruit of pumpkin used to treat hepatitis manner pumpkin fruit cut into small pieces and then steamed, then eaten .Pumpkin fruits contain active compounds such as saponins, tannins, flavonoids and beta-carotene. Beta-carotene is converted in the body into vitamin A is beneficial for the growth, maintenance of body tissues and to reduce the risk of cancer and heart disease. This study aims to determine pumpkin juice has a hepatoprotective activities on liver function by looking at parameters SGPT and SGOT in rats after induced CCl4. Type of experimental research using True Experimental research design design. Test animals were grouped into 5 groups, each group consisting of 3 rats. The first group of positive control (Methicol®), the second group negative control (CCl4), the third group of pumpkin juice 25%, the fourth group of pumpkin juice 50%, the fifth group of pumpkin juice 75%. From the results of this study concluded that the pumpkin juice 75% effective as a hepatoprotective by looking at parameters SGPT is 48 U/liter and SGOT is 66 U/liter in rats after induced carbon tetrachloride